Taxonomic notes and lectotypification of Sporobolus tetragonus Bor (Poaceae, Chloridoideae) - Senniappan, Arumugam; Murthy, Garimella Venkata Suryanarayana; Nair, Velukutty Jayachandran (Phytotaxa, 2018)
Sporobolus Brown (1810:169.) Poaceae, Chloridoideae is represented by c. 160 species widely distributed in the tropical and subtropical regions of the world (Clayton & Renvoize 1986). Hooker (1896) reported 13 species in the Flora of the British India. Bor (1960) recognized 22 species in The Grasses of Burma, Ceylon, India and Pakistan. However, for the current political boundaries of India, Karthikeyan et al. (1989) recorded a total of 18 species. During the taxonomic revision of Sporobolus in India, we found that majority of the specimens of S. tetragonus Bor (1949: 25) were mistakenly identified and also there is a need for the selection of a lectotype. Therefore, the taxonomy and lectotypification of this species are discussed in the present paper.